Care, Support and Therapy Service of HIV Patients with the “SATE Krembung” Application - Totok Indarto; Arif Rahman Nurdianto; Dyah Ayu Febiyanti (Jurnal Ners, 2019)
Introduction: The prevalence and incidence of HIV and AIDS in Sidoarjo is still high. Today, the adherence of patients to several ART services in Sidoarjo is quite low and varied. Therefore the researchers want to find out the effectiveness of registration using “the SATE Krembung” application in terms of service effectiveness, reducing the Lost Follow Up (LFU) and increasing patient adherence in Krembung Primary Health Care.Methods: The study was cross-sectional. The use of alternative ART service modes was done via “the SATE Krembung” application as an integrated queue system. The patients who participated in this study were HIV patients at Krembung Primary Health Care who accessed ART at Krembung Primary Health Care within the age range of 20 - 60 years. The total number of samples in this test was 16 patients.Results: Registration using “the SATE Krembung” application can reduce the waiting time for getting access to services for the HIV patients who plan on getting CST services and ART collection.Conclusion: Service effectiveness due to the use of “the SATE Krembung” application can improve service quality, reduce the Lost Follow Up (LFU) and increase the patient adherence in Krembung Primary Health Care’s ART services.